"Living in Contaminated Areas"—Consideration of Different Perspectives. Issue 1 (July 2020) - Abend, Michael; Nisbet, Anne; Gering, Florian; Averin, Viktor; Andersson, Kasper; Schneider, Thierry; Mothersill, Carmel; Zeeb, Hajo; Scholz-Kreisel, Peter; Yamashita, Shunichi; Pölz-Viol, Christina; Port, Matthias
Abstract : Abstract: Following large-scale nuclear power plant accidents such as those that occurred at Chernobyl (Ukraine) in 1986 and Fukushima Daiichi (Japan) in 2011, large populations are living in areas containing residual amounts of radioactivity. As a key session of the ConRad conference, experts were invited from different disciplines to provide state-of-the-art information on the topic of "living in contaminated areas." These experts provided their different perspectives on a range of topics including radiation protection principles and dose criteria, environmental measurements and dose estimation, maintaining decent living and working conditions, evidence of health risks, and social impact and risk communication. A short summary of these different perspectives is provided in this paper.